Analisis Sistem Informasi Akuntansi dalam Meningkatkan Pengendalian Internal Keuangan - Marliana Juliyanti; Rama Gita Suci (Universitas Muhammadiyah Metro, 2026)
This study aims to analyze the accounting information system at Zainab Mother and Child Hospital and determine how effective internal financial controls are at RSIA Zainab. The type of research used is descriptive-qualitative research. The data used in this research is primary data and secondary, which was collected through interviews, observation, and documentation. The results showed that the information system for improving internal control at the Zainab Mother and Child Hospital has been running effectively in accordance with the provisions of the Sharia-based Accounting and Financial Guidelines. All operational activities have been computerized using the SIMRS system and Accurate. However, there are still weaknesses, such as SIMRS and accuracy, which often cause errors during input. Then the cashier's income input is still done manually by separating inpatient and outpatient income so that it allows recording and inputting errors. The existence of these obstacles can slow down the workings of the system, so it is necessary to improve the system and software so that the company's operational activities can run smoothly without being constrained by the system.